Image of Kazakh Officials in Materials of Oral Literature (Journal of history, 2019)
In the article, the author examines the problem of the Kazakh bureaucracy in the materials of oral folk art of the second half of the XIX – early XX centuries. And the works of akyns-poets of that period are analyzed. In the first part of the article, the author examined the works of akyns-improvisers and zhyrau, and in the second part – poems written by poets of the Kazakh people. In their works, attention was paid to the problems of Kazakh officials, their activities and the electoral system, corruption and arbitrariness on the part of the volosts and biys. In addition, in the final part, the author, on the basis of the materials studied, gives his own statements regarding the images of Kazakh officials.